Gandhi - Saklani, Juhi. (New York, New York : DK Publishing, 2014)
A biography of Mahatma Gandhi, the Indian political and spiritual leader who led his country to freedom from British rule through his policy of nonviolent resistance.
Includes index.
008-012.
Keywords: Gandhi, -- Mahatma, -- 1869-1948; Nationalists -- India -- Biography -- Juvenile literature; Nonviolence -- India -- History -- 20th century -- Juvenile literature; Pacifists -- India -- Biography -- Juvenile literature; Statesmen -- India -- Biography -- Juvenile literature; India -- Politics and government -- 1919-1947 -- Juvenile literature